The Influence of the Associated Inactivated Vaccine Against Infectious Rhinotracheitis and Bovine Viral Diarrhea on the Formation and Duration of Colostral Immunity in Kazakh Whiteheaded Calves - Yerbol Bulatov; Alina Kurmasheva; Zhanat Amanova; Ruslan Abitaev; Zhanna Sametova; Asselya Kyrgyzbayeva; Zhanat Kondybaeva; Sholpan Turyskeldi; Abdurakhman Ussembay; Dariya Toktyrova; Dana Mazbayeva; Yeraly Shayakhmetov; et al. (Vaccines)
Objectives: This article presents a study evaluating the antibody levels against infectious bovine rhinotracheitis (IBR) and bovine viral diarrhea (BVD) in Kazakh Whiteheaded calves born to dams immunized with an experimental inactivated combined vaccine against these infections. The vaccine formulation includes the strains “R-93” (IBR) and “Oregon C24V” (BVD), which are preserved in the microorganism collection of the Research Institute for Biological Safety Problems. Methods: To assess the immune response in newborn calves, blood serum samples were collected before the first intake of colostrum, followed by weekly sampling for 28 weeks post-birth. The antibody response was determined using a virus neutralization assay on MDBK cell cultures and lamb testicle cell cultures. Results: The results demonstrated that the protective antibody level against the IBR virus (≥2 log2) persisted for up to 25 weeks, while the protective level against the BVD virus (≥3 log2) remained for 23 weeks. Based on these findings, the vaccine was deemed safe, as it did not induce abortions or clinical manifestations of the diseases. The overall duration of the colostral immunity in calves against the IBR and BVD viruses reached 23 weeks. Conclusions: Therefore, it is recommended that Kazakh Whiteheaded calves be vaccinated with the associated inactivated vaccine against infectious bovine rhinotracheitis and bovine viral diarrhea no earlier than 23 weeks of age.